Effects of short light/dark cycles on photosynthetic pathway switching and growth of medicinal Dendrobium officinale in aeroponic cultivation - Cheng, Yongsan; He, Dongxian; He, Jie; Niu, Genhua; Ji, Fang (International Journal of Agricultural and Biological Engineering, 2019)
Dendrobium officinale has high medicinal value but grows slowly in natural environment due to its special CAM photosynthetic pathway. In this study, D. officinale were grown aeroponically with light/dark cycles of 12 h/12 h, 4 h/4 h, and 2 h/2 h for 150 d. The photosynthetic electron transfer characteristics, photosynthetic CO2 fixation pathways, and accumulations of biomass and soluble polysaccharides in D. officinale leaves were studied. The results showed that the photosynthetic apparatus states of D. officinale in aeroponic cultivation under short light/dark cycles of 4 h/4 h and 2 h/2 h were better than that under 12 h/12 h. The dark net CO2 exchange percentages of D. officinale were negative in short light/dark cycles of 4 h/4 h and 2 h/2 h, and the daily net CO2 exchange amount and dry/fresh weight increases were doubled compared with those in 12 h/12 h light/dark cycle. High soluble polysaccharides content and the soluble polysaccharides yield of D. officinale were obtained in the shorter light/dark cycle of 2 h/2 h. Therefore, the photosynthetic pathway of D. officinale could be switched from CAM to C3 by short light/dark cycles of 4 h/4 h and 2 h/2 h, and its higher biomass accumulation and soluble polysaccharides yield could be obtained by the shorter light/dark cycle of 2 h/2 h in aeroponic cultivation. Keywords: dark net CO2 exchange percentage, photosynthetic pathway, short light/dark cycle, soluble polysaccharides DOI: 10.25165/j.ijabe.20191205.4864 Citation: Cheng Y S, He D X, He J, Niu G H, Ji F. Effects of short light/dark cycles on photosynthetic pathway switching and growth of medicinal Dendrobium officinale in aeroponic cultivation. Int J Agric & Biol Eng, 2019; 12(5): 38–43.